The Effectiveness of Utilization of Local Raw Materials as Feed to Increase Productivity of Catfish (Clarias sp.) in Sakatiga Village, Indralaya District, Ogan Ilir Regency, South Sumatra - Mohamad Amin; Ferdinand Hukama Taqwa; Yulisman Yulisman; Retno Cahya Mukti; Madyasta Anggana Rarassari; Rizky Marli Antika (Journal of Aquaculture and Fish Health, 2020)
Sakatiga Village, located in Indralaya District, Ogan Ilir Regency, South Sumatra, has the potential to develop aquaculture. Problems often experienced by fish farmers in the village of Sakatiga include the high price of feed and the lack of public knowledge about local materials that can be used as raw material for fish feed. These problems can be overcome by making feed independently. The purpose of this activity is to evaluate the effectiveness of the utilization of local materials as a raw material for feed to an increase in the productivity of catfish (Clarias sp.) in Sakatiga village, Indralaya District, Ogan Ilir Regency, South Sumatra. The method used is counseling and discussion, training in making food and a demonstration plot using local materials as raw material for fish food and technical assistance by the team and assisted by students who carry out field practices at partner locations. Based on the results obtained indicate an increase in community knowledge about local materials that can be used as fish food and community motivation to make feed using local raw materials. Utilization of local raw materials as catfish feed yields an absolute weight and length growth of 9.94 g and 3.83 cm respectively, a daily growth rate of 2.21%/day, feed efficiency of 103.24% and survival of 97%.